Improvement of carrier diffusion length in silicon nanowire arrays using atomic layer deposition - Kato, Shinya (Springer, 2013)
To achieve a high-efficiency silicon nanowire (SiNW) solar cell, surface passivation technique is very important because a SiNW array has a large surface area. We successfully prepared by atomic layer deposition (ALD) high-quality aluminum oxide (Al2O3) film for passivation on the whole surface of the SiNW arrays. The minority carrier lifetime of the Al2O3-depositedSiNW arrays with bulk silicon substrate was improved to 27 μs at the optimum annealing condition. To remove the effect of bulk silicon, the effective diffusion length of minority carriers in the SiNW array was estimated by simple equations and a device simulator. As a result, it was revealed that the effective diffusion length in the SiNW arrays increased from 3.25 to 13.5 μm by depositing Al2O3 and post-annealing at 400°C. This improvement of the diffusion length is very important for application to solar cells, and Al2O3 deposited by ALD is a promising passivation material for a structure with high aspect ratio such as SiNW arrays.